Interfacial stability and intermixing in thin-layer sin/gen superlattices - Kelires, Pantelis C. (My University, 1994)
Using energies obtained from empirical-potential calculations, we study the relative stability between abrupt, ordered, and randomized interfaces in thin-layer superlattices. For most of the substrate parameter values, both ordered and randomized layers are more stable than the abrupt interface. The ordered geometries have even lower formation enthalpies than random structures. We examine the implications of these results in view of experimental studies of annealing and interdiffusion.
Keywords: Energy; Enthalpy